Intradermal immunization with botulinum neurotoxin serotype E DNA vaccine induces humoral and cellular immunity and protects against lethal toxin challenge - Na Young Kim; Hye Bin Ahn; Chi Ho Yu; Dong Hyun Song; Gyeung Haeng Hur; Young Kee Shin; Sungho Shin (Taylor & Francis Group, 2019)
Botulinum neurotoxins (BoNTs) produced by the spore-forming, gram-positive, anaerobic bacterium Clostridium botulinum are the most toxic substances known and cause botulism, flaccid paralysis, or death. Owing to their high lethality, BoNTs are classified as category A agents by the Centers for Disease Control (CDC). Currently, there are no vaccines available to protect against BoNTs, so the rapid development of a safe and effective vaccine is important. DNA-based vaccines have recently drawn great attention because they can be developed quickly and can be applied in mass vaccination strategies to prevent disease outbreaks. Here, we report on the immunogenic and protective efficacy of a DNA vaccine, encoding a 50-kDa carboxy-terminal fragment of the BoNT serotype E heavy chain, which is delivered via an intradermal route. This plasmid DNA vaccine induced robust humoral and cellular BoNT/E-specific immune responses and completely protected animals against lethal challenge with BoNT/E. These results not only indicate that DNA vaccines could be further developed as safe and effective candidates for vaccines against BoNTs but also suggest a possible approach for developing vaccines that protect against bio-threat toxins.